PEARR tool training and implementation: building awareness of violence and human trafficking in a hospital system - Roe-Sepowitz, Dominique; Bracy, Kristen; Gibbs, Holly; Stafford, Rae Lynn; Bernardin, Brooke; Stoklosa, Hanni (Frontiers in Medicine, 2024)
Introduction Health professionals have an opportunity to assist patients who are experiencing many types of violence, including human trafficking; however, current approaches are often not person-centered. The Provide privacy, Educate, Ask, Respect and Respond (PEARR) Tool, a recognized screening tool in the U.S., is a structured conversation guide for health professionals on how to provide trauma-sensitive assistance to patients who may be experiencing such violence, including human trafficking. This is the first study to evaluate the PEARR Tool and its use in hospital settings. Methods A U.S.-based health system adopted the PEARR Tool as part of its Abuse, Neglect, and Violence policy and procedure. To support successful adoption, the health system also developed educational modules on human trafficking and trauma-informed approaches to patient care, including a module on the PEARR steps. In October 2020 and June 2021, a voluntary “PEARR Tool Training and Implementation Survey” was distributed to emergency department staff in three hospitals. The survey consisted of 22 questions: eight demographic and occupation related questions; five questions related to the education provided to staff; and, nine questions related to the use of the PEARR Tool in identifying and assisting patients. Results The overall findings demonstrate a general increase in awareness about the prevalence of human trafficking, as well as a significant increase in awareness about the implementation of the PEARR Tool. However, the findings demonstrate that most respondents were not utilizing the PEARR Tool between October 2020 and June 2021. Most reported that the reason for this was because they had not suspected any of their patients to be victims of abuse, neglect, or violence, including human trafficking. Of those that had utilized the PEARR Tool, there was a marked increase in staff that reported its usefulness and ease of access when caring for patients. Discussion The COVID-19 pandemic posed many challenges during this study, including delays in staff education, changes in education format and delivery, and strains on staff. Initial data regarding the use of the PEARR Tool is promising; and additional research is recommended.